Evaluation of Vaccine Cold Chain Storage at the Ciracas Community Health Center - Arif Rahmandani; Dalia Jamal; Alfa Michael Gabriel Koraag; Rahmatul Qodriah; Dani Rianto (Journal of Social Research, 2026)
Vaccination is one of the most effective public health interventions for preventing vaccine-preventable diseases; however, vaccine effectiveness depends greatly on maintaining proper cold-chain management from storage to administration. Inadequate vaccine storage conditions may reduce vaccine potency and compromise immunization programs. This study aimed to evaluate the suitability of vaccine cold-chain storage management at the Ciracas Community Health Center based on the Guidelines for Vaccine Management in Health Care Facilities. This research employed a qualitative descriptive method through direct observation and evaluation using an observation checklist instrument. Data were collected by assessing vaccine storage facilities, infrastructure, storage conditions, temperature monitoring, vaccine arrangement, maintenance practices, and supporting management systems. The results showed that vaccine storage management at the Ciracas Community Health Center achieved a conformity score of 73%, categorized as “fairly good.” Several components met the required standards, including temperature monitoring, the availability of trained vaccine management personnel, stock rotation using the First-Expiry, First-Out (FEFO) system, and routine maintenance activities. However, several deficiencies were identified, including the absence of a dedicated freezer, inadequate air circulation, improper separation of expired vaccines, insufficient refrigerator spacing, and suboptimal vaccine arrangement. In conclusion, vaccine storage practices at the Ciracas Community Health Center were generally acceptable but still required continuous improvement to ensure vaccine quality, safety, and effectiveness. Strengthening infrastructure, improving storage procedures, and conducting periodic evaluations are recommended to optimize cold-chain management.